2D numerical study of wave and current-induced oscillatory non-cohesive soil liquefaction around a partially buried pipeline in a trench. (1st May 2017) - Duan, Lunliang; Liao, Chencong; Jeng, Dongsheng; Chen, Linya
Abstract: This paper proposes a two-dimensional (2D) coupled model for wave and current-seabed-pipeline interactions to examine oscillatory non-cohesive soil liquefaction around a partially buried pipeline in a trench. Unlike previous studies, two new features are included in this model: (1) wave-current interactions around the pipeline; and (2) fully coupled processes for the wave and current-seabed-pipeline system. In this study, the Reynolds Averaged Navier-Stokes (RANS) equations are applied to simulate the flow field around the pipeline, and Biot's poro-elastic theory for porous media is imposed to govern the soil response due to the wave-current loading. After being validated using data available in the literature, the 2D model is used to investigate the effects of the current velocity, the soil properties, and the wave characteristics on oscillatory non-cohesive soil liquefaction. Using the model, a function for the critical backfill thickness and the wave steepness under various flow and soil conditions is proposed to facilitate engineering practice. Highlights: A coupled model for wave (current)-seabed-pipeline interaction is proposed. The liquefaction zone around pipeline is related to wave and soil characteristics. Current velocity affects soil response around a partially buried pipeline. Backfills thickness plays an important role in the liquefaction potential.